THE EFFECTIVENESS OF BEHAVIORAL COUNSELING WITH TOKEN ECONOMY AND BEHAVIOR CONTRACT TECHNIQUES TO REDUCE ACADEMIC PROCRASTINATION - Sidiq, Muhamad; Mulawarman, Mulawarman; Awalya, Awalya (Study Program of Guidance and Counseling, Postgraduate Program, Universitas Negeri Semarang, 2020)
Academic procrastination makes students? learning outcomes low. As a result, they may not make it to the next level or even be expelled. Accordingly, this study was intended to examine the effectiveness of behavioral counseling with token economy and behavior contract techniques to reduce the academic procrastination of the students of SMP IT Insan Cendekia Semarang. The study was experimental and used repeated measure design. The subjects were 16 students chosen using purposive sampling. Further, the data of this study were collected through students? academic procrastination scale. After the analysis, there found that the experimental group with behavior contract technique gained higher reduction than the token economy group. Thus, counselors are suggested to apply token economy, and behavior contract in guidance and counseling services.